Konvergensi dan Tipologi Makna Humor sebagai Konstruksi Konteks Komunikasi Ala Gen Z: Perspektif Ekolinguistik - Krismonika,; Aidha, Fakhriyyah Asmay (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Ecolinguistics perspectives have point of views to analyzing phenomenon from the environment impacts beside humor languages as forms of communication are affected by human society, culture, and the technological environment as a place of communication. This research explores the meaning of convergence and typology humor languages in Gen Z conversation and also the digital environment contextual forms the understanding and reception of humor presented. This study uses quantitative methods to more understand and know society phenomena, culture, and human behavior in depth. Particularly, inside humor language as Gen Z communication construction. The qualitative methods using reading methods to research and collect data with notes technique. The building element in linguistics cannot be left alone without the influence of the social and natural environment around it. There are three building elements in linguistics that are nature’s connection with humans, the setting or environment, and the local wise principles. In the context of Gen Z, ecolinguistics indicates that the digital environment helps to shape the language used in daily life so that the resulting term not only reflects the identity of the generation but also conveys a particular symbolic meaning. New terms produced in the ward not only represent the identity of the generation but also contain symbolic meanings that reflect the pattern of thought and values held including appreciation for nature.